The Influence of Liquidity and Profitability on Returns Shares in Coal Sub-Sector Companies That Listed on The Indonesian Stock Exchange In 2018-2021 - Gina Meiliani; Seflidiana Roza; Esi Sriyanti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to determine the effect of liquidity on stock returns, the effect of profitability on stock returns, and the effect of liquidity and profitability on stock returns in coal sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021. The type of research used is quantitative research. The data used is secondary data obtained via the website www.idx.co.id. The sample consisted of 23 companies that published complete financial reports for 4 years (2018-2021). The sampling technique used was purposive sampling, so that 92 data were obtained.The research results show that Liquidity variables do not have a significant influence on stock returns. Meanwhile, the Profitability Variable has a significant influence on Stock Returns. Simultaneously, it is found that Liquidity and Profitability both have a simultaneous influence with R2 of 0.209 (20.9%) Keywords: Liquidity, Profitability and Stock Returns